Fibulin-2 is a key mediator of the pro-neurogenic effect of TGF-beta1 on adult neural stem cells - Radice, Pablo Daniel (2015)
Transforming growth factor beta 1 (TGF-beta1), an anti-inflammatory cytokine, has been shown to have pro-neurogenic effects on adult Neural Stem Cells (aNSC) from the dentate gyrus and in vivo models. Here, we expanded the observation of the pro-neurogenic effect of TGF-beta1 on aNSC from the subventricular zone (SVZ) of adult rats and performed a functional genomic analysis to identify candidate genes to mediate its effect. 10 candidate genes were identified by microarray analysis and further validated by qRT-PCR. Of these, Fibulin-2 was increased 477-fold and its inhibition by siRNA blocks TGF-beta1 pro-neurogenic effect. Curiously, Fibulin-2 was not expressed by aNSC but by a GFAP-positive population in the culture, suggesting an indirect mechanism of action. TGF-beta1 also induced Fibulin-2 in the SVZ in vivo. Interestingly, 5 out of the 10 candidate genes identified are known to interact with integrins, paving the way for exploring their functional role in adult neurogenesis. In conclusion, we have identified 10 genes with putative pro-neurogenic effects, 5 of them related to integrins and provided proof that Fibulin-2 is a major mediator of the pro-neurogenic effects of TGF-beta1. These data should contribute to further exploring the molecular mechanism of adult neurogenesis of the genes identified and the involvement of the integrin pathway on adult neurogenesis.